Elections in 2020: What did city hall candidates propose for the environment? (Research, Society and Development, 2022)
The electoral process means a decisive moment in the creation, closure, or continuity of practices related to the socio-environmental agenda. Assuming the relevance of that context, the objective of this work is to evaluate how the environmental issue was contemplated in government plans of city hall candidates in the elections in 2020. We randomly selected three cities to evaluate, but representing a specific populational range (small, medium and big city). We developed a method that evaluates the approach related to the environment in the government plans for candidates for the city hall, being nine categories (solid waste management, water resources management, sanitation, air quality, climate change, green areas, biodiversity, sustainable development, and environmental education). We interactively defined the categories, based on environmental and public policy management scientific literature and reading the government plans. Each category was evaluated in a 0-3 scale and each plan received a final grade that represents the sum of the values of the nine categories. The environmental issue approach in the government plans was limited and below what was expected. Four plans did not mention the environmental issue and the less addressed categories were air quality, climate change and biodiversity. In some cases, the proposals showed that they have electoral interest and maybe don’t mean a legitimate environmental concern. This study did not approach partisan political issues or the application of the proposals, being these potential fields for future work.